Molecular characterization of extrahepatic cholangiocarcinoma: perihilar and distal tumors display divergent genomic and transcriptomic profiles. (2nd December 2021) - Simbolo, Michele; Bersani, Samantha; Vicentini, Caterina; Taormina, Sergio V.; Ciaparrone, Chiara; Bagante, Fabio; Rusev, Borislav; Centonze, Giovanni; Montresor, Marina; Brunelli, Matteo; Pedron, Serena; Mafficini, Andrea; et al.
ABSTRACT: Background: Extrahepatic cholangiocarcinoma (ECC) is classified into two subtypes based on anatomic origin: distal extrahepatic (DECC) and perihilar (PHCC) cholangiocarcinoma. This study aimed to shed light on its genomic and transcriptomic profiles. Research Design and Methods: The genomic alterations of 99 ECC (47 PHCC and 52 DECC) were investigated by next-generation sequencing of 96 genes. A subgroup of cases, representative of each subtype, was further investigated using transcriptomic analysis. Bioinformatics tools were applied for clustering and pathway analysis and defining the immune composition of the tumor microenvironment. Results: PHCC had more frequent KRAS mutations (p = 0.0047), whereas TP53 mutations were more common in DECC (p = 0.006). Potentially actionable alterations included high-tumor mutational burden and/or microsatellite instability (7.1%), PI3KCA mutations (8.1%), and MYC (10.1%) and ERBB2 amplification (5.1%). The transcriptomic profiles showed the presence of three distinct clusters, which followed the anatomic origin and differed in immune microenvironment. DECC appeared to contain two distinct tumor subgroups, one enriched for druggable alterations and one lacking actionable opportunities. Conclusions: This study provides new insights into the molecular landscape and the actionable alterations of ECC. Our findings represent a step toward improved ECC molecular taxonomy and therapeutic strategies for precision oncology.